(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: Hydraulic structures such as dams, canals, and reservoirs significantly alter the natural environment and ecological balance in their vicinity. These transformations impact water quality, biodiversity, sediment transport, and local microclimates. This article reviews the main ecological changes caused by hydraulic infrastructure and discusses contemporary methods for monitoring and assessing these impacts. Emphasis is placed on integrated approaches combining remote sensing, field surveys, and modeling techniques to provide comprehensive evaluations necessary for sustainable water resource management and ecological conservation.